Kemunculan Lingua Sacra dalam Sejarah al-Qur’an (Perspektif John Wansbrough) - Musaddad, Asep (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
The language of the Qur’an has long been disputed in the history of Qur’anic exegesis. It particularly related to the discourse of Arabic rhetoric and in turn has also sparked a considerable controversy especially in the context of “kalam” sectarianism (madhhab kala>mi>). John Wansbrough, a famous Western scholar, is one of those who paid much attention on the issue in his monumental work, Qur’anic Studies. The work is regarded as one of the exponents of the “historical-critical” study of the Quran that contains several key issues, including the intersection of the Qur’an with Arabic rhetoric discourse, which in turn is also responsible for the emergence of sacred sense in the two domains. Starting with Wansbrough’s key issues on Qur’anic Studies, this article provides a brief introduction to his thought about the emergence of the concept of the sacred language (lingua sacra) in the history of the Qur’an and some of the implications thereof. Keywords: John Wansbrough, lingua sacra, rhetorical exegesis, majaz.